ANALISIS KOMPARASI KINERJA KEUANGAN BANK UMUM SYARIAH DENGAN PENDEKATAN METODE CAMEL - Listriyani, Futri; Wartoyo, Wartoyo; Setiowati, Nur Eka (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2024)
This study aims to compare the performance levels of two Islamic commercial banks in Indonesia, namely Bank BCA Syariah and Bank Muamalat Indonesia for the period 2018 to 2022. This study uses a method that is often used to analyze the level of performance of Islamic banking, namely the CAMEL method. The indicators in this study consist of five financial ratios, namely CAR, NPF, NPM, ROA, and FDR. This research uses quantitative methods with comparative research types. Using secondary data from financial reports published on the official website of each bank. Kolmogorov-Smirnov test is used for data normality testing and hypothesis testing using independent t-test and Mann-Whitney test. The results showed statistically significant differences in the values of CAR, NPF, ROA, and FDR in Islamic banking between Bank BCA Syariah and Bank Muamalat Indonesia, then there was no significant difference in the NPM ratio between the two banks. Based on the results described, Bank BCA Syariah has a superior average value in terms of CAR, NPF, NPM and ROA ratios compared to Bank Muamalat Indonesia. Meanwhile, the performance of Bank Muamalat Indonesia's FDR proportion is better than Bank BCA Syariah in recent years. Therefore, it can be said that Bank BCA Syariah and Bank Muamalat Indonesia have different performance.Keywords: Financial Performance; Islamic Banks; Camels Method